Precision Medicine and the Role of Biomarkers of Radiotherapy Response in Breast Cancer - Meehan, James; Gray, Mark; Martínez-Pérez, Carlos; Kay, Charlene; Pang, Lisa Y.; Fraser, Jennifer A.; Poole, Amy V.; Kunkler, Ian H.; Langdon, Simon P.; Argyle, David; Turnbull, Arran K. (Frontiers in Oncology, 2020)
Radiotherapy remains an important treatment modality in nearly two thirds of all cancers, including the primary curative or palliative treatment of breast cancer. Unfortunately, largely due to tumour heterogeneity, tumour radiotherapy response rates can vary significantly, even between patients diagnosed with the same tumour type. Although in recent years significant technological advances have been made in the way radiation can be precisely delivered to the gross tumour volume, it is proving more difficult to personalise radiotherapy regimens based on tumour biology. Biomarkers that provide prognostic or predictive information regarding a tumour’s intrinsic radiosensitivity or its response to treatment could prove valuable in helping to personalise radiation dosing, enabling clinicians to make decisions between different treatment options whilst avoiding radiation-induced toxicity in patients unlikely to gain therapeutic benefit. Studies have investigated numerous ways in which both patient and tumour radiosensitivities can be assessed. Tumour molecular profiling has been used to develop radiosensitivity gene signatures, while the assessment of specific intracellular or secreted proteins, including circulating tumour cells, exosomes and DNA, has been performed to identify prognostic or predictive biomarkers of radiation response. Finally, the investigation of biomarkers related to radiation-induced toxicity could provide another means by which radiotherapy could become personalised. In this review, we discuss studies that have used these methods to identify or develop prognostic/predictive signatures of radiosensitivity, and how such assays could be used in the future as a means of providing personalised radiotherapy.